Efetivação judicial dos direitos econômicos, sociais e culturais - Lima, George Marmelstein (2005)
This essay studies the role of the Judiciary branch in the implementation process of the economic, social and cultural rights (ESC Rights), like the right to health care, education, housing etc. The goal of the study consists of an analysis of what the judges can do to enforce the implementation of the ESC Rights without interfering with the functions and responsibilities of the other branches (Executive and Legislative), that are, in a democracy, the main branches responsible for implementing social policies. Based on a favorable opinion about the fundamental rights and the judicial review, it defends an active role of the judges in the search for maximum efficiency of the social rights entrenched in the Constitution and in the international treaties. The study of the doctrine and the jurisprudence, in Brazil and in other countries, indicates that there is a tendency for a larger acceptance of the justiciability of the ESC Rights, especially in the developing countries. In these countries, the democratic institutions, like the parliament and the government elected by the people, are incapable of reducing the social injustices. Therefore, the Judiciary becomes a concrete hope of implementation of the socio-economics goals established in the Constitution. In this context, arises the possibility of enforcement of the ESC Rights by the judges. However, to accept the possibility of the judicial enforcement of these rights demands the development of creative solutions to overcome the obstacles that appear in the compliance of the judicial order. The essay proposes some strategies to implement the ESC Rights in the judicial arena, based on the experience of many courts around the world.